DDX58 deficiency leads to triple negative breast cancer chemotherapy resistance by inhibiting Type I IFN-mediated signalling apoptosis - Cao, Shiyu; Long, Xinyi; Xiao, Lin; Zhang, Peichuan; Shen, Mengjia; Chen, Fei; Bao, Chunjuan; Zhong, Xiaorong; Luo, Ting; Ye, Feng (Frontiers in Oncology, 2024)
Triple-negative breast cancer (TNBC) is characterized by its aggressive nature and absence of specific therapeutic targets, necessitating the reliance on chemotherapy as the primary treatment modality. However, the development of drug resistance poses a significant challenge in the management of TNBC. In this study, we investigated the role of DDX58 (DExD/H-box helicase 58), also known as RIG-I, in TNBC chemoresistance. Initially, our analysis revealed that patients with lower expression of DDX58 led to lower rate of pathological complete response (pCR) and worse prognosis by online databases and hospital clinical data. Subsequently, DDX58 knockdown (DDX58-KD) cells showed multiple chemo-drugs resistance (paclitaxel, doxorubicin, 5-fluorouracil) in TNBC cell lines. Similarly, DDX58 knockout (DDX58-KO) cells also showed multiple chemo-drugs resistance in a dosage-dependent manner. Additionally, in the CDX model, tumours in the DDX58-KO group had a 25% reduction in the tumour growth inhibition rate (IR) compared to wild-type (WT) group after doxorubicin (Dox) treatment. The depletion of DDX58 inhibited proliferation and promoted the migration and invasion in MDA-MB-231 cells. The findings of our research indicated that DDX58-KO cells exhibit a reduction in Dox-induced apoptosis both in vivo and in vitro. Mechanistically, Dox treatment leads to a significant increase in the expression of double-stranded RNAs (dsRNAs) and activates the DDX58-Type I interferon (IFN) signaling pathway, ultimately promoting apoptosis in TNBC cells. In summary, our study highlights the role of DDX58 in mediating chemotherapy-induced apoptosis and identifies a novel pathway of chemotherapy resistance in TNBC, suggesting the potential for personalized treatment strategies based on DDX58 expression levels.